Analysis of Judicial Application of Criminal Penalty Against Notary / Land Deed Officials Conducting Making Crime of the Fake Authentic Deed in State Court of Semarang - Mohammad Barkah Arrohim; Haris Wahyu Sunarno; Sri Endah Wahyuningsih (Jurnal Akta, 2020)
The purpose of this study was to: 1) analyze the application of criminal penalty against Notary / PPAT in the crime of counterfeiting deed on the Case In State Court of Semarang. 2) Analyze the legal consequences of the Notary / PPAT penalized following criminal of fake deed as object case in court on a lawsuit in State Court of Semarang. The approach in this research is normative juridical that while the data used in this research primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Based on the results of data analysis concluded that: 1) The application of criminal law to the Notary / PPAT in the crime of falsification of the authentic deed in case Criminal judges are viewed from the indictment, formally defendant has fulfilled the elements formulation in forgery and materially to hear and see information from the defendant, the witnesses and the evidence presented in the trial and have sufficient minimum of two (2) valid evidence, the defendant was found guilty and convincingly to have committed the crime of falsification of the authentic Article 264 of the criminal Code in conjunction with Article 55 (1) e of the criminal Code that is alleged to defendant ,2) The legal consequences of the Notary / PPAT sanctioned criminal in the crime of counterfeiting authentic deed along with the deed that made the object of a case in court on the case Criminal defendant Notary / PPAT sentenced to prison with a prison sentence and All certificates issued by the defendant Notary / PPAT canceled in favor law.Keywords: Criminal Penalty; Notary / PPAT; Authentic Deed.